Regional variation in mineral content, cytotoxicity, and antioxidant activity of Aerodramus fuciphagus nests from different districts in Kelantan, Malaysia. - Sul’ain, Mohd Dasuki; Isah, Musa; Abdul Wahab, Wan Nor Amilah Wan (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to assess Aerodramus fuciphagus (Thunberg, 1812) nest’s mineral content, cytotoxicity effects, and antioxidant activity. The Edible birds’ nests (EBNs) were obtained from Tanah Merah (TM), Tumpat (TU), and Jeli (JE) districts in Kelantan, Malaysia. Materials and Methods: The mineral content was assessed via inductively coupled plasma mass spectrometry. The cytotoxicity effect was evaluated by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide and brine shrimp lethality assays. The antioxidant activity was investigated by 2,2´-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging and ferric-reducing antioxidant power (FRAP) assays. Results: Valuable macro- and microelements, including sodium, potassium, aluminum, calcium, magnesium, zinc, iron, and selenium, were detected in the EBN samples. The cytotoxicity test revealed that JE hydrochloric acid (HCl) extract had promising efficacy against HeLa cell lines, with IC50 values of 20.00 ± 0.57 µg/ml. Similarly, TU sodium hydroxide (NaOH) extract inhibited the proliferation of MCF-7 cell lines (IC50 0.03 ± 0.01 µg/ml). Based on the BSL assay, the EBNs were considered safe for consumption as the LC50 values of all the samples were below the toxic level (>1,000 µg/ml). TM EBNs aqueous, TU aqueous, and HCl extracts showed promising antioxidant activity at IC50 values (10 µg/ml) in the DPPH assay. However, the NaOH extract from TU exhibited the highest FRAP value (1.38 ± 0.00 mM gallic acid equivalents gm⁻¹) compared to all other extracts. Conclusion: This study’s findings demonstrated the potential of EBN as an alternative anticancer agent and natural antioxidant. J. Adv. Vet. Anim. Res., 12(1): 132–140, March 2025 http://doi.org/10.5455/javar.2025.l880